Investigando o mitogenoma de Trichoderma harzianum: evolução, perfil transcricional e mecanismos regulatórios - Paula Luize Camargos Fonseca (2021)
Mitochondria is a cytoplasmic organelle found in most eukaryotic cells and are responsible for respiration and cellular homeostasis. The mitochondrial genome (mitogenome) has been the subject of studies in comparative genetics and evolution, since it has conserved genes among all species, as well as variations in intronic and repetitive regions. The order Hypocreales is composed of fungal species that perform several ecological functions, which can be saprobes, pathogens or mutualistic. One of the prominent species is Trichoderma harzianum, which has been widely used in biological control of other fungi and nematodes. The first chapter of this thesis aimed to investigate the variability and evolution of 35 mitogenomes from the order Hypocreales. Variation in structure and size of mitogenomes were correlated with the presence of non-coding regions. Evolutionary analysis has estimated that fast-evolving mitogenomes have a larger non-coding region. Additionally, some intron sequences are conserved among species, suggesting horizontal transfer processes. Despite the variation in size and noncoding content, the mitogenomes evaluated have a group of conserved genes, with the ribosomal gene rns is being the only one containing one exon. The genetic conservation, the number of copies per cell and their presence in most eukaryotic organisms, make them a potential molecular marker for taxonomic classification of species. In chapter two, we evaluated whether the rns gene for the identification of fungal species from Hypocreales. The sequences of rns were compared to other genes commonly used to identify Hypocrealean fungi, including the genus Trichoderma, which has numerous cryptic species, as a case study. The results suggested that the rns gene, despite separating all the Hypocrealean species, is not sufficient for the correct identification of all the Trichoderma isolates. Nonetheless, the use of rns and calmodulin genes proved to be an efficient combination for the identification of species from the genus. Mitochondria, in spite of having their own genome, need genes encoded in the nucleus for their functioning. Much of the knowledge about the genes involved in their regulation is specific only to model organisms, such as Homo sapiens, Neurospora crassa or Saccharomyces cerevisiae. Nevertheless, some studies have already demonstrated in N. crassa the absence of genes identified in H. sapiens and S. cerevisiae, which are fundamental for mitogenome control. Thus, with the objective of expanding knowledge about mitogenome control mechanisms, the results of sequencing, assembly, and annotation of the T. harzianum nuclear genome, and the presence of genes with location in the mitochondria was investigated and